2020
DOI: 10.3390/nano10030443
|View full text |Cite
|
Sign up to set email alerts
|

Improving Formation Conditions and Properties of hBN Nanosheets Through BaF2-assisted Polymer Derived Ceramics (PDCs) Technique

Abstract: Hexagonal boron nitrite (hBN) is an attractive material for many applications such as in electronics as a complement to graphene, in anti-oxidation coatings, light emitters, etc. However, the synthesis of high-quality hBN at cost-effective conditions is still a great challenge. Thus, this work reports on the synthesis of large-area and crystalline hBN nanosheets via the modified polymer derived ceramics (PDCs) process. The addition of both the BaF2 and Li3N, as melting-point reduction and crystallization agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…The hexagonal boron nitride (hBN) nanosheets were synthesised based on the reported procedure, whereby borazine was used a source for boron and nitrogen atoms, lithium nitride (Li 3 N, 99.4%, Alfa Aesar) [26,27], and barium fluoride (BaF 2 , 99%, Alfa Aesar) [28]. Typically, pure borazine monomer was polymerized at 55 • C to generate a colourless liquid polyborazylene (PBN) [28,29]. Then, 5 wt.% Li 3 N and 0-10 wt.% BaF 2 [30] were added to PBN, and the suspension was homogenised for 10 min.…”
Section: Materials Synthesis and Sensor Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The hexagonal boron nitride (hBN) nanosheets were synthesised based on the reported procedure, whereby borazine was used a source for boron and nitrogen atoms, lithium nitride (Li 3 N, 99.4%, Alfa Aesar) [26,27], and barium fluoride (BaF 2 , 99%, Alfa Aesar) [28]. Typically, pure borazine monomer was polymerized at 55 • C to generate a colourless liquid polyborazylene (PBN) [28,29]. Then, 5 wt.% Li 3 N and 0-10 wt.% BaF 2 [30] were added to PBN, and the suspension was homogenised for 10 min.…”
Section: Materials Synthesis and Sensor Preparationmentioning
confidence: 99%
“…The morphology of the device active materials was investigated using transmission electron microscopy (TEM), which showed that the hBN samples were mainly overlapping, well-defined, and plate-like nanostructures of 0.89 ± 0.01, 2.9 ± 0.7, 3.3 ± 0.3, and 3.2 ± 0.7 µm in dimension for pristine hBN nanoflakes as well as the modified hBN samples after modification with 2.5, 5, and 10 wt.% of BaF 2 , respectively (Figure 1). The improvement in hBN nanosheets size upon addition of BaF 2 to the pre-ceramization mixture can be attributed to the faster melting of Li 3 N. This was facilitated by BaF 2 [28], consequently leading to improved crystallisation of hBN from PBN. As such, the effect of the addition of BaF 2 to crystallinity and textual properties of the hBN nanosheets was studied using Raman spectroscopy and BET analysis.…”
Section: Structural Analysismentioning
confidence: 99%
See 3 more Smart Citations